EFFECT OF REPLACEMENT OF SOYBEAN MEAL BY SILKWORM MEAL ON GROWTH PERFORMANCE, APPARENT METABOLIZABLE ENERGY AND NUTRIENT DIGESTIBILITY IN BROILERS AT DAY 28 POST HATCH - R. Ullah; S. Khan; N. A. Khan; M. Tahir; N. Ahmad (Journal of Animal and Plant Sciences, 2018)
This study evaluated the effect of replacing soybean meal with silkworm meal on production performance, apparent metabolizable energy (AME) and apparent nutrients digestibility in broiler during starter phase. Fiveiso-nitrogenous and iso-caloric diets were formulated by stepwise i.e. 0% (SM0) , 25% (SM25), 50% (SM50), 75% (SM75) and 100% ( SM100) replacement of soybean meal with silkworm meal in broiler ration. Two hundred and fifty broiler day-old chicks were divided into twenty-five replicate groups ( n=10), with five replicates per diet using a completely randomized design. The silkworm meal analysis showed higher levels of crude protein ( 57.6 ± 1.50%) and crude fat (23.3 ± 0.21%). The silkworm meal has higher contents (g/100g of total amino acids) of lysine (7.52 ± 0.376) and methionine ( 3.88 ± 0.376), but was slightly deficient in tryptophan ( 1.70 ± 0.413). Mean intake of feed, gain in body weight and dressing percentage were higher (P < 0.05) in group SM75 in comparison with other groups. Moreover, better (P < 0.05) FCR was observed for SM0 ( 1.58± 0.031) and SM75 ( 1.59 ± 0.071) groups than SM50 (1.62 ± 0.030) group. The AME was higher (P < 0.05) in group SM75 and SM100 in comparison with other groups. The digestibility of dry matter, crude protein, crude fat, ash and N free extract did not differ (P > 0.05) . The organoleptic quality parameters were not altered ( P > 0.05) due to replacement of soybean meal by silkworm meal. The findings of the present study revealed that silkworm meal may effectively be used by replacing 75% soybean meal as low-cost protein ingredient in broiler ration. 2017). Recent studies have demonstrated that commercial
Keywords: Protein source; Insect protein; Amino acid profile; Feed conversion ratio.